US Markers and Necroinflammation, Steatosis, and Fibrosis in Metabolic Dysfunction-associated Steatotic Liver Disease: The iLEAD Study - Sugimoto, Katsutoshi; Moriyasu, Fuminori; Burgio, Marco Dioguardi; Vilgrain, Valérie; Jesper, Daniel; Strobel, Deike; Blank, Valentin; Karlas, Thomas; Grant, Edward G.; Kelahan, Linda C.; Gabriel, Helena; Choi, Byung Ihn; et al. (Radiology, 2024)
Background: Attenuation coefficient (AC) and shear-wave speed (SWS) are established US markers for assessing patients with metabolic dysfunction-associated steatotic liver disease (MASLD), while shear-wave dispersion slope (DS) is not. Purpose: To assess the relationship between the multiparametric US imaging markers DS, AC, and SWS and liver histopathologic necroinflammation in patients with MASLD. Materials and Methods: This international multicenter prospective study enrolled consecutive patients with biopsy-proven MASLD between June 2019 and March 2023. Before biopsy, all participants underwent multiparametric US, and measurements of DS, AC, and SWS were obtained. Multivariable linear regression analyses were performed to assess the association of clinical variables and imaging markers with pathologic findings. The diagnostic performance of imaging markers for determining inflammation grade, steatosis grade, and fibrosis stage was assessed using the area under the receiver operating characteristic curve (AUC). Results: A total of 124 participants (mean age, 53 years ± 15 [SD]; 62 males) were evaluated. In multivariable regression, lobular inflammation was associated with DS (regression coefficient, 0.06; P = .02), alanine aminotransferase level (regression coefficient, 0.002; P = .002), and Hispanic or Latino ethnicity (regression coefficient, -0.68; P = .047), while steatosis was associated with AC (regression coefficient, 3.66; P < .001) and fibrosis was associated with SWS (regression coefficient, 2.02; P < .001) and body mass index (regression coefficient, 0.05; P = .02). DS achieved an AUC of 0.72 (95% CI: 0.63, 0.82) for identifying participants with inflammation grade A2 or higher (moderate to severe inflammation). AC showed excellent performance for identifying participants with grade S1 (mild) or higher steatosis (AUC, 0.92 [95% CI: 0.87, 0.97]), while SWS showed excellent performance for identifying participants with fibrosis stage F2 or higher (clinically significant fibrosis) (AUC, 0.91 [95% CI: 0.86, 0.96]). Of the three US markers, SWS showed the highest AUC (0.81 [95% CI: 0.74, 0.89]) for the diagnosis of metabolic dysfunction-associated steatohepatitis. Conclusion: Of the three US imaging markers (DS, AC, and SWS), DS was most associated with lobular inflammation grade at histologic examination and demonstrated fair diagnostic performance in distinguishing moderate to severe lobular inflammation.
CRIS-Team Scopus Importer:2024-09-13